Innovation and marketing performance of SME in an emerging economy: The moderating effect of transformational leadership - Samuel Afriyie; Jianguo Du; Abdul-Aziz Ibn Musah (Journal of Global Entrepreneurship Research, 2019)
This paper aims to draw on the resource-based view (RBV) to examine the effect of transformational leadership (TL) on innovation and marketing performance in SME service firms. The paper further investigates the extent to which transformational leadership influences the effect of innovation on marketing performance and how such an effect could be managed for SME development. Cross-sectional survey data were collected from 437 SME service firms of an emerging economy with a fast-growing service sector. The quantitative methodologies were used in which partial least squares structural equation modeling (PLS-SEM) with bootstrap procedures was adopted to test the hypotheses. The findings suggest that innovation has a positive effect on marketing performance; transformational leadership has a moderating effect on the relationship between innovation and marketing performance. The study's results show that these effects are robust in the firm's marketplace. The current study examined the TL effect based on each rating. Therefore, it would be useful to study the effects of TL and other variables that can be manipulated by team level dynamics (or groups) such as trust in the team, team creativity, and team innovative performance in the future. For SME to be highly competitive in emerging economies, this study deepens the effect of innovation on firm performance and as such managers/owners should consider the vital role of transformational leadereship as a predictor of the relationship between innovation types and marketing performance. This current study contributes to the literature by assessing a valid model that describes the relationships between transformational leadership on innovation and marketing performance concurrently. This is the first empirical study to focus on SME marketing performance concerning types of innovation and marketing performance in an emerging economy with a moderated effect of transformational leadership.
Keywords: 650; Innovation; Transformational leadership; Marketing performance; PLSSEM; Moderation analysis